Access to Art: Bridging the Gap Between Urban and Rural Communities in Indonesia’s Art Scene (Indonesian Art and Justice Review, 2024)
In Indonesia, there is a notable disparity in access to art and artistic education between urban and rural communities. This paper investigates the barriers to equitable access to art in the country, focusing on the uneven distribution of resources, opportunities, and exposure to artistic practices. The study analyzes how the concentration of artistic institutions and markets in major urban centers like Jakarta and Yogyakarta limits rural communities’ participation in the art scene. It also explores initiatives and grassroots movements aimed at bridging this gap, including mobile art education programs, community-based art projects, and online platforms. The paper argues for the importance of inclusive art policies that ensure all Indonesians, regardless of their geographic location, can access and participate in the cultural economy.